A profile of MPA students' perceptions of online learning: What MPA students value in online education and what they think would improve online learning experiences. (2nd January 2021) - Ni, Anna Ya; Van Wart, Montgomery; Medina, Pamela; Collins, Kimberly; Silvers, Ernest; Pei, Hang
ABSTRACT: What do MPA students value in online education and what do they think would improve online learning experiences in an MPA program? Ironically, few studies have tried to derive more than a couple of factors in a single study. Integrating the key concepts from across the literature, the perceptions about an array of quality factors were identified and studied both quantitatively and qualitatively with a survey of 160 MPA students. The results distinguish and rank seven factors affecting students' perceptions of quality online education in a theoretically coherent framework. Those factors are: basic online modality, teaching presence, instructional support, interactive online modality, social presence, cognitive presence, and trust in the online teaching system. The overall impressions of online learning examined include the degree of online acceptance, the likelihood of taking online classes, and the effects of instructional skill.